Hubungan Personal Hygiene dengan Gejala Dermatitis pada Narapidana di Lembaga Pemasyarakatan Kelas II A Jambi Tahun 2024 - rahmadiah, aisyah; Amir, Andy; Hidayati, Fajrina; Guspianto, Guspianto; Eka Putri, Fitria (Jurnal Kesmas Jambi, 2024)
The national prevalence of dermatitis in Indonesia based on Basic Health Research data by the Ministry of Health 2018 is 6.8% and tends to increase every year. Data from the Jambi Provincial Health Service, in 2021 dermatitis was ranked eighth with the most common disease with a percentage of 5.03%, while in 2022 it experienced an increase and was ranked sixth with a percentage of 5.96%. This research aims to determine the relationship between personal hygiene and symptoms of dermatitis in prisoners at the Class IIA Jambi Penitentiary in 2024. This research is a quantitative study using a cross sectional study design. The sampling technique used Proportionate Random Sampling on 1124 prisoners at the Class IIA Jambi Penitentiary by conducting interviews. The cleanliness of prisoners' clothing was in the good category for 37.2% of respondents. Towel cleanliness was in the good category as many as 41.5% of respondents. Inmates with good bed cleanliness were 47.9% of respondents. Hand and nail cleanliness was in the good category for 56.4% of respondents